2011
DOI: 10.1007/s10815-011-9697-3
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stimulation and embryo banking for fertility preservation in a woman with severe mixed connective tissue disease: is it safe?

Abstract: Objective To report the first case of using assisted reproductive technologies (ART) for fertility preservation in a patient with mixed connective tissue disease (MCTD), secondary pulmonary hypertension (PH) and antiphospholipid syndrome (APS). Design Case-report and review of the literature. Setting Academic infertility practice and tertiary care center. Patient(s) A 25-year-old woman with MCTD, complicated with PH and APS, who was scheduled for gonadotoxic therapy Intervention(s) Controlled ovarian hyperstim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(40 reference statements)
0
5
1
Order By: Relevance
“…Severe complications were reported in a 25‐year‐old woman with an acute phase of mixed connective tissue disease. After an oocyte cryopreservation procedure for fertility preservation, she presented with a cascade of multiorgan system dysfunctions probably exacerbated by increased estradiol levels and the sedation required for oocyte retrieval . Hence, the risk of multiorgan complications can be life‐threatening in patients in the acute phase of the disease.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe complications were reported in a 25‐year‐old woman with an acute phase of mixed connective tissue disease. After an oocyte cryopreservation procedure for fertility preservation, she presented with a cascade of multiorgan system dysfunctions probably exacerbated by increased estradiol levels and the sedation required for oocyte retrieval . Hence, the risk of multiorgan complications can be life‐threatening in patients in the acute phase of the disease.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…After an oocyte cryopreservation procedure for fertility preservation, she presented with a cascade of multiorgan system dysfunctions probably exacerbated by increased estradiol levels and the sedation required for oocyte retrieval. 42 Hence, the risk of multiorgan complications can be life-threatening in patients in the acute phase of the disease. To avoid these risks, some authors have suggested collecting immature oocytes during a natural menstrual cycle, followed by in vitro maturation and vitrification.…”
Section: Autoimmune D Is E a S E Smentioning
confidence: 99%
“…According to research conducted by Noman et al (2017), credit risk, loan ratio, cost efficiency, and capitalization negatively affect the market share of Islamic banking. At the same time, Contessi et al (2013) and Sioulas & Gracia (2012) found that capitalization has a significant positive effect on market share.…”
Section: Hypothesis Competitiveness Capitalization Financing Risk And...mentioning
confidence: 91%
“…I have read with great interest the recent demonstrative case report by Sioulas & Gracia on ovarian stimulation and embryo banking for fertility preservation in a woman with severe mixed connective tissue disease [MCTD] [1], and congratulate the authors for their integrity and self criticism. The authors correctly emphasize the life threatening complications associated with pulmonary hypertension and IVF in MCTD, as dramatically demonstrated by their case report.…”
mentioning
confidence: 99%
“…Therefore this treatment should be considered and recommended to every young woman before gonadotoxic chemotherapy. The authors [1] mention the possibility "…that GnRH may exacerbate autoimmune diseases, an association that merits further research ". The answer to their raised question has been supplied by others and by us [2,4,5].…”
mentioning
confidence: 99%